Development of natural product based flocculant agent to treat petroleum refinery industry wastewater - Mariah, Che Mamat (2015)
Spent caustic or used caustic soda generated from the scrubbing process in the petroleum refinery industry. Treatment is needed for spent caustic because it typically has high chemical demand (COD), oil-grease (OG) and Biochemical oxygen demand (BOD5) concentration, pH and temperature that exceeded the limit of Department of Environment (DOE) regulations. In this study, the spent caustic was treated by using adsorption method by using natural product such as charcoal and coconut husk based flocculants agent in batch mode. The benefits of natural product usage is a green technology approaches and cheaper. The treated spent caustic was tested for its COD, OG and BOD5 concentration, pH also the temperature to determine respectively the percentage of reduëtion measured using Spectrophotometer, Standard 5520B liquid-liquid partition-gravimetric method, Dissolved Oxygen meter (DO meter), and pH meter. Results show COD concentration for untreated spent caustic is at a range of 4910 - 13980 mg/L, OG concentration is 32 - 6285 mg/L, BOD5 concentration at range of 41 - 78 mg/L, pH at a range of 11.9 - 13.0, and temperature at range 20 °C - 29 °C. The highest percentages reduction by using charcoal and coconut husk was able to reduce 50.38 % (6885 mg/L) and 45.19 % (7605 mg/L) COD, 46.88 % (17 mg/L) and 21.88 % (25 mg/L) OG, 55.13 % (35 mg/L) and 45.51 % (42 mg/L) BOD5 , 60.05 % (5.15) and 48.02 % (6.70) pH, 20.88 % (23 °C) and 4.0 % (28 °C) temperature respectively. The optimum amount in large scale by using charcoal and coconut husk is 600 g and 800 g based flocculants agent soda ash, alum, and ferum sulphate that have a ratio of 0.05:0.42:0.53 with activated carbon and clay as additional adsorbents that have a ratio of 0.74:0.26, which able to reduced 91.78 % (1140 mg/L) and 81.19 % (2610 mg/L) COD concentration by recycle in eight times respectively. Flocculants agent was used in pre-treatment in order to increase adsorption method efficiency of natural product. Hence, natural product by using charcoal is more efficient than coconut husk. The information obtained from this study is useful for scale up purpose in the petroleum refming industry that choose adsorption method by using natural products based flocculants agent to treat spent caustic wastewater.